Method and system for image pre-processing - KALEVO OSSI; KAKKORI HANNU (2011)
An imaging architecture has a memory module to store raw images for the pre-processing stage. The raw image from the output of the pre-processing block may be compressed by a compressor before the image is stored in the memory module. Furthermore, the raw image in the memory is subject to pre-processing as many times as needed or desired. Thus, a decompressor may be operatively connected to the memory module to retrieve the stored image and to decompress the retrieved image before providing the image to the pre-processing block. In the imaging architecture, a loop formed by the memory module, the decompressor, the pre-processing block and the compressor allows the image to be pre-processed multiple times. The imaging architecture can be coupled to the main processor and post-processor in an imaging device for further processing the image data for display or for transmission.